2021
DOI: 10.1111/liv.15006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between frailty and cirrhosis etiology: From the Functional Assessment in Liver Transplantation (FrAILT) Study

Abstract: Background & Aims Cirrhosis leads to malnutrition and muscle wasting that manifests as frailty, which may be influenced by cirrhosis aetiology. We aimed to characterize the relationship between frailty and cirrhosis aetiology. Methods Included were adults with cirrhosis listed for liver transplantation (LT) at 10 US centrer who underwent ambulatory testing with the Liver Frailty Index (LFI; ‘frail’ = LFI ≥ 4.4). We used logistic regression to associate aetiologies and frailty, and competing risk regression (LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…The importance of these considerations is even more critical in light of the evolving epidemiology of LT candidates due to the increased prevalence of non-alcoholic steatohepatitis (NASH). A recent study investigating the relationship between frailty and cirrhosis etiology revealed that NASH patients were the frailest category of LT candidates, justifying particular attention to the liver functional reserve and malnourishment and immunologic impairment when a patient is transplanted (40).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of these considerations is even more critical in light of the evolving epidemiology of LT candidates due to the increased prevalence of non-alcoholic steatohepatitis (NASH). A recent study investigating the relationship between frailty and cirrhosis etiology revealed that NASH patients were the frailest category of LT candidates, justifying particular attention to the liver functional reserve and malnourishment and immunologic impairment when a patient is transplanted (40).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among frail people, those with NFS score F3/F4 had a significantly greater hazard for dementia over a long period, as indicated in a multivariable model adjusted for clinical and laboratory parameters [ 40 ]. Recently, Xu et al , analyzing data from cirrhotic patients awaiting LT, showed that NAFLD patients had a higher median liver frailty index (LFI) compared to their non-NAFLD counterparts [ 41 ]. Moreover, the prevalence of frailty was higher in the NAFLD group of patients [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Xu et al , analyzing data from cirrhotic patients awaiting LT, showed that NAFLD patients had a higher median liver frailty index (LFI) compared to their non-NAFLD counterparts [ 41 ]. Moreover, the prevalence of frailty was higher in the NAFLD group of patients [ 41 ]. Nonetheless, in the multivariate analysis, adjusted for age, model for end-stage liver disease-sodium score and ascites, only ALD and other causes of liver disease were independently associated with frailty, whereas NAFLD was marginally correlated with frailty (P=0.05).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of these considerations is even more critical in light of the evolving epidemiology of LT candidates due to the increased prevalence of non-alcoholic steatohepatitis (NASH). A recent study investigating the relationship between frailty and cirrhosis etiology revealed that NASH patients were among the frailest category of LT candidates, justifying specific consideration to the liver functional reserve and malnourishment and immunologic impairment when a patient is transplanted ( 5 ).…”
mentioning
confidence: 99%